Effect of road transportation on the serum biochemical parameters of cynomolgus monkeys and beagle dogs - OCHI, Takehiro (J Vet Med Sci, 2016)
To determine the effect of long-distance (approximately 600 km) road transportation on the blood biochemistry of laboratory animals, we investigated the changes in serum biochemical parameters in healthy cynomolgus monkeys and beagle dogs transported by truck from Osaka to Tsukuba, Japan. The concentrations of serum cortisol, total bilirubin and aspartate aminotransferase in monkeys increased during transportation. Serum cortisol and total bilirubin levels in dogs also increased during transportation, but serum triglyceride decreased. Serum parameter values in truck-transported monkeys and dogs returned to baseline levels within two weeks following arrival. Taken together, these results suggest that a two-week acclimation period is the minimum duration required for adaptation following road transportation.